The Effectiveness of Concept Mapping on Social Skills of Students in Social Learning of Elementary School (Journal of Primary Education, 2019)
The purpose of this study was; to analyze the achievement of social skills of students who experienced in learning using the concept mapping. This study is expected to improve teacher performance in learning by looking at the appropriate approach to learning social studies (IPS). This type of research used is a quantitative research method in the form of quasi-experimental design with pre-test – post-test control group design. The population of this study was all grade IV elementary school students in Pattimura Cluster, Genuk Sub-District, Semarang City. The sample was selected through a purposive sampling technique, so that selected SDN Karangroto 03 class IVA as the experimental group and class IV B as the control group. Data collection techniques use non-test techniques which include interview guidelines, observation guidelines, and documentation. The results of the study indicate that; the method of concept mapping effectively increases the social skills of students in social studies learning in the fourth grade of elementary school, with the achievement of 2 indicators namely; (1) the improvement of students' social skills is in the minimum medium category based on the N-Gain test in the experimental class. The results of the N-Gain test in the experimental class are 0.32 which are classified into the medium category; and (2) the average score for concept mapping is in the minimum, medium category. The results of the average making of the concept mapping by students are 78% in the high category.